The Emerging Roles of Early Protein Folding Events in the Secretory Pathway in the Development of Neurodegenerative Maladies - Dubnikov, Tatyana; Cohen, Ehud (Frontiers in Neuroscience, 2017)
Although protein aggregation and deposition are unifying features of various neurodegenerative disorders, recent studies indicate that different mechanisms can lead to the development of the same malady. Among these, failure in early protein folding and maturation emerge as key mechanistic events that lead to the manifestation of a myriad of illnesses including Alzheimer’s disease and prion disorders. Here we delineate the cascade of maturation steps that nascent polypeptides undergo in the secretory pathway to become functional proteins, and the chaperones that supervise and assist this process, focusing on the subgroup of proline cis/trans isomerases. We also describe the chaperones whose failure was found to be an underlying event that initiates the run-up towards neurodegeneration as well as chaperones whose activity impairs protein homeostasis (proteostasis) and thus, promotes the manifestation of these maladies. Finally, we discuss the roles of aggregate deposition sites in the cellular attempt to maintain proteostasis and point at potential targets for therapeutic interventions.